The synergistic effect of the triglyceride-glucose index and a body shape index on cardiovascular mortality: the construction of a novel cardiovascular risk marker - Hao-ming He; Ying-ying Xie; Qiang Chen; Yi-ke Li; Xue-xi Li; Sun-jing Fu; Na Li; Yan-ru Han; Yan-xiang Gao; Jin-gang Zheng (Cardiovascular Diabetology)
Abstract Background Insulin resistance, represented by increased triglyceride-glucose (TyG) index levels, shows interplay with visceral obesity and together promotes cardiovascular diseases and mortality. However, significant controversies exist regarding whether modified TyG indices, such as TyG-BMI, TyG-WC, and TyG-WHtR, outperform the TyG index in predicting cardiovascular outcomes. We aimed to explore whether there was a synergistic effect of a body shape index (ABSI), a better parameter reflecting visceral obesity, and the TyG index on cardiovascular mortality. Methods We analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2001–2018 of 17,329 individuals. The associations of the TyG index and ABSI with cardiovascular mortality were investigated via Cox regression analysis and restricted cubic splines. Receiver operating characteristic (ROC) curve analysis was performed to compare the predictive value. Mediation analysis was used to explore the potential mediator. Results A total of 673 (3.9%) cardiovascular deaths occurred during a median follow-up of 8.92 years. Individuals with high TyG and high ABSI (TyG > 9.04 and ABSI > 0.085) were at the highest cardiovascular mortality risk both in individuals with (HR = 1.714, 95% CI 1.123–2.616) and without diabetes (HR = 1.402, 95% CI 1.003–1.960), suggesting a synergistic effect. Next, we multiplied these two indicators and established TyG-ABSI. It showed a J-shaped relationship and a positive linear relationship with cardiovascular mortality in individuals with and without diabetes, respectively. Arterial stiffness, represented by estimated pulse wave velocity, partially mediated the effect of TyG-ABSI on cardiovascular mortality, with a mediation proportion of 42.7%. The predictive value of TyG-ABSI was greater than that of the TyG index, TyG-BMI, TyG-WC, and TyG-WHtR (Harrell’s C-index: 0.710 vs 0.623 vs 0.539 vs 0.612 vs 0.622, all p < 0.001). Conclusions The simultaneous assessment of the TyG index and ABSI revealed a synergistic effect on cardiovascular mortality. We recommended the use of TyG-ABSI instead of the TyG index and other modified TyG indices in cardiovascular risk assessment.